2013
DOI: 10.1021/jz402025n
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Nitrate As Regenerable SEI Stabilizing Agent for Rechargeable Li/O2 Batteries

Abstract: A major unsolved problem with rechargeable Li/O2 batteries is the identification of electrolyte compositions that allow efficient and stable cycling of both Li metal and O2 electrodes simultaneously. Previously, lithium nitrate (LiNO3) was employed in a rechargeable Li/O2 battery to stabilize the solid–electrolyte interphase on Li metal in an electrolyte based on N,N-dimethylacetamide (DMA), a solvent with favorable properties vis-à-vis the O2 electrode. We show that LiNO3 is regenerated following reaction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
112
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 18 publications
8
112
0
3
Order By: Relevance
“…This result is in good agreement with those for LiNO 3 -based electrolytes, in which the NO 3 − anion acts as a mild oxidant for the Li metal NE to form a stable oxide film. [29][30][31] Thus, the Li dissolution/deposition reaction rate depends on the formation of an Li oxide layer, containing Li 2 CO 3 , on the Li metal NEs. This suggests that control of the oxidation state of the Li metal NE surface is key to enhance and maintain good LAB performance.…”
Section: Resultsmentioning
confidence: 99%
“…This result is in good agreement with those for LiNO 3 -based electrolytes, in which the NO 3 − anion acts as a mild oxidant for the Li metal NE to form a stable oxide film. [29][30][31] Thus, the Li dissolution/deposition reaction rate depends on the formation of an Li oxide layer, containing Li 2 CO 3 , on the Li metal NEs. This suggests that control of the oxidation state of the Li metal NE surface is key to enhance and maintain good LAB performance.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, using quantitative measures of battery rechargeability, high-DN solvents, such as DMSO and N-methyl pyrrolidone, have been observed to be less stable than low-DN solvents, such as acetonitrile and DME (14). Recently, Khetan et al used a thermodynamic analysis to show that an organic solvent's ability to induce the solution mechanism is anticorrelated with its stability toward nucleophilic attack (15 (16,17). We found that electrolytes containing a high concentration of NO 3 − exhibited higher donicity, as verified using 7 Li NMR, and provided an increase in battery capacity greater than fourfold compared with a battery using exclusively TFSI − as the electrolyte anion, while not decreasing battery rechargeability, as measured using quantitative oxygen consumption and evolution.…”
Section: Significancementioning
confidence: 99%
“…There are many studies that use LiNO 3 in conjunction with other RMs to further improve battery performance . However, LiNO 3 only works in the presence of Li metal because LiNO 2 would be spontaneously oxidized in the presence of O 2 to LiNO 3 and it is not stay stable as LiNO 2 in the cell …”
Section: Redox Mediators For Chargementioning
confidence: 99%
“…[36] However,LiNO 3 only works in the presence of Li metal because LiNO 2 would be spontaneously oxidized in the presence of O 2 to LiNO 3 and it is not stay stable as LiNO 2 in the cell. [37]…”
Section: Other Rm Charmentioning
confidence: 99%